Dietary resin acid composition as a performance enhancer for broiler chickens. (27th February 2017) - Kettunen, H.; van Eerden, E.; Lipiński, K.; Rinttilä, T.; Valkonen, E.; Vuorenmaa, J.
Summary: Resin acid composition (RAC) has previously been shown to inhibit the growth of the Gram-positive bacterial species Clostridium perfringens in vitro and to modulate the ileal microbiota of broiler chickens. The following trials examined the effect of RAC on broiler chickens in two experiments. In experiment 1, 1400 one-day-old Ross 308 broilers were divided into two coccidiostat treatments: chemical (CC) and ionophore (IC), which were further divided into two RAC dosages: 0 and 0.5 g/kg. All diets were supplemented with xylanase, β-glucanase and phytase feed enzymes. The birds were raised in a commercial-type environment without additional microbial challenge during the 42-day trial. RAC improved the body weight gain by 3.3% and feed conversion ratio by 5.7% with CC, and improved footpad lesion scores with IC but had no effect on the litter quality. Experiment 2 was a 35-day subclinical necrotic enteritis (NE) challenge trial with 510 male Ross 308 chickens. The dietary treatments included a non-challenged, non-supplemented control and four NE challenged treatments with dietary RAC supplementation at 0, 1, 2, and 3 g/kg. The birds were challenged with Eimeria maxima on day nine and C. perfringens on day 14. While RAC at 1 g/kg significantly increased bird weight gain during the challenge, it did not affect the microbial or short chain fatty acid (SCFA) profiles. In contrast, RAC at 3 g/kg reduced the abundance of the Lactobacillus group and tended to reduce the abundance of genus Bifidobacterium and the total numbers of eubacteria. These experiments suggest that dietary RAC at a moderate dose positively affected broiler performance. However, changes in caecal microbiota populations may not have influenced the observed performance effects of RAC.